(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study investigates the linguistic and stylistic characteristics of military discourse in contemporary Uzbek and English fiction, focusing on five key novels: “Daryo ortidagi yig‘I” by Qo‘chqor Norqobil, “Quyosh qoraymas” by Oybek, “Qonli yo‘rgaklar” by Abdurashid Nurmurodov, and James Jones’s “The Thin Red Line” and “From Here to Eternity”. Using a philological approach that combines lexical-semantic analysis with discourse theory, the paper explores how authors construct meaning through vocabulary choices, stylistic devices, and narrative strategies. The analysis reveals that military fiction often employs emotionally charged expressions, war-related metaphors, and narrative techniques such as irony, fragmentation, and reader interaction. In Uzbek novels, traditional rhetorical figures like repetition and culturally embedded metaphors are prominent, reflecting themes of national identity and sacrifice. In contrast, Jones’s novels use military jargon, colloquial language, and shifting perspectives to depict psychological turmoil and institutional power dynamics. The study also categorizes the war theme’s presence in texts as macro-, meso-, or micro-inclusions, showing varying degrees of thematic centrality. A key concept is the lexical-semantic space (LSS), which frames the text as a network of meaning shaped by both authorial intention and reader interpretation. The findings highlight that military fiction, shaped by postmodernist tendencies and historical context, serves not only to narrate war but to provoke reflection on its moral, psychological, and cultural impact. Ultimately, this research contributes to a deeper understanding of how language in war literature encodes ideology, emotion, and collective memory.